2004
DOI: 10.1007/s00394-004-0466-2
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A exerts its activity at the transcriptional level in the small intestine

Abstract: Our results suggest that vitamin-A deficiency modifies the maturation and differentiation processes of the small intestinal mucosa at the transcriptional and post-transcriptional levels respectively. This in turn may be one explanation for the alteration or elimination of nutrient digestion and absorption during VAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Broadly, the microarray data on gene expression showed that vitamin A deficiency is a catabolic state that might in part be due to decreased nutrient availability [7]. Increased plasma FFAs stimulates PPARa-controlled pathways, which generally promote fat oxidation or export as lipoproteins, and inhibits SREBP-1-regulated genes, which are involved in fat synthesis; both of these changes were detected in the vitamin A-deficient rats of this study ( Table 6).…”
Section: Effects On Metabolismmentioning
confidence: 75%
See 1 more Smart Citation
“…Broadly, the microarray data on gene expression showed that vitamin A deficiency is a catabolic state that might in part be due to decreased nutrient availability [7]. Increased plasma FFAs stimulates PPARa-controlled pathways, which generally promote fat oxidation or export as lipoproteins, and inhibits SREBP-1-regulated genes, which are involved in fat synthesis; both of these changes were detected in the vitamin A-deficient rats of this study ( Table 6).…”
Section: Effects On Metabolismmentioning
confidence: 75%
“…Decreased IGF-1 levels are also seen in starvation and calorie or diet restriction [5,6]. The effects of diet and vitamin A deficiency on IGF-1 may be related because vitamin A deficiency changes enzyme levels and histology of the small intestine accompanied by increased inflammation that can lead to decreased absorption of nutrients and decreased growth [7]. The liver is the major storage organ for retinol and is involved in most aspects of vitamin A homeostasis.…”
Section: Introductionmentioning
confidence: 95%
“…an increased proportion of immature enterocytes). Indeed, changes in the maturation of epithelial cells can involve both transcriptional and post-transcriptional regulation of disaccharidase enzymes (8, 29). …”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, we reported that VAD induces morphological and functional changes in chicken and rat small intestines [5][6][7].…”
Section: Introductionmentioning
confidence: 99%